Calcium-dependent protein kinase CDPK16 phosphorylates serine-856 of glutamate receptor-like GLR3.6 protein leading to salt-responsive root growth in Arabidopsis# - Silamparasan, Dhanasekar; Chang, Ing-Feng; Jinn, Tsung-Luo (Frontiers in Plant Science, 2023)
Calcium-permeable channels in the plasma membrane play vital roles in plant growth, development, and response to environmental stimuli. Arabidopsis possesses 20 glutamate receptor-like proteins that share similarities with animal ionotropic glutamate receptors and mediate Ca2+ influx in plants. Calcium-dependent protein kinases (CDPKs) phosphorylate serine (Ser)-860 of glutamate receptor-like (GLR)3.7 protein, which interacts with 14-3-3ω and plays an essential role in salt and abscisic acid response in Arabidopsis by modulating Ca2+ signaling. However, the significance of CDPK- mediated phosphorylation status of Ser residues of GLR3.6 with regard to the functioning of GLR3.6 remains to be elucidated. In this study, we performed an in vitro kinase assay using CDPK16 and peptides containing the 14-3-3ω interacting domain of GLR3.6. We showed that Ser861/862 of GLR3.6 are required for the interaction with 14-3-3ω and that Ser856 of GLR3.6 is specifically phosphorylated by CDPK16 but not by CDPK3 and CDPK34. In addition, the expression of GLR3.6 was quickly downregulated by salt stress, and plants of glr3.6 mutants and GLR3.6-overexpression lines presented shorter and longer root lengths, respectively, under normal growth conditions than Col. Overexpression of the GLR3.6-Ser856 to Ala mutation resulted in a less sensitive phenotype in response to salt stress similar to glr3.6. Our results indicated that the Ser861/862 residues of GLR3.6 are required for interaction with 14-3-3ω. Additionally, the phosphorylation status of Ser856 residue of GLR3.6, which is mediated specifically by CDPK16, regulates root growth in normal and salt stress and conditions.